Diospyros lotus-mediated Synthesis of Iron Oxide Nanoparticles and Their Application as a Catalyst in Fenton Reaction - Batool, Sadaf; Hussain, Zakir (Current Nanoscience, 2020)
Background: Iron Oxide nanoparticles have enormous applications in environmental remediation and catalysis. The synthesis of such nanoparticles through a green approach provides a significant advantage due to the non-toxic nature of the ingredients involved. Methods: In the present work, Diospyros lotus fruit extract was used for the synthesis of iron oxide nanoparticles (NPs). The plant biomolecules were extracted employing two different solvents, i.e. water and methanol. The effect of both the extracts on the reduction of metal salt as well as on the shape and size of the produced NPs was investigated. Results: UV-Visible spectroscopy confirmed the synthesis of iron oxide NPs, Fourier Transform Infrared (FTIR) spectrum depicted the presence of biomolecules on the surface of NPs as capping agents, X-ray Diffraction (XRD) diffractogram confirmed the crystalline structure of mixed iron oxide NPs and Scanning Electron Microscopy (SEM) images showed the spherical shape of NPs. The synthesized NPs were exploited to catalyze the degradation of methylene blue dye in the Fenton type catalytic reaction. The degradation reaction was monitored using UV-Visible spectroscopy, which indicated that the percent degradation increased from 15% (without iron oxide NPs) to 91% in the presence of organic extract prepared iron oxide NPs and to 81% in the presence of aqueous extract prepared iron oxide NPs. The effect of the concentration of methylene blue and iron oxide NPs on the degradation process was also investigated. Conclusion: The results indicated the potential of synthesized nanoparticles to promote catalytic reactions involved in environmental remediation.
Keywords: iron oxide nanoparticles